A Theory of Monopolistic Competition with Horizontally Heterogeneous Consumers - Sergey Kokovin; Alina Ozhegova; Shamil Sharapudinov; Alexander Tarasov; Philip Ushchev (Center for Economic Studies and ifo Institute (CESifo), 2023)
Our novel approach to modeling monopolistic competition with heterogeneous firms and consumers involves spatial product differentiation. Space can be interpreted either as a geographical space or as a space of characteristics of a differentiated good. In addition to price setting, each firm also chooses its optimal location in this space. We formulate conditions for positive sorting: more productive firms serve larger market segments and face tougher competition; and for the existence and uniqueness of the equilibrium. To quantify the role of the sorting mechanism, we calibrate the model using cross-sectional haircut market data and perform counterfactual analysis. We find that inequality in the distribution of the gains among consumers caused by positive market shocks can be substantial: the gains of consumers from more populated locations are 3-4 times higher.
Keywords: F10; L11; L13; 330; firm heterogeneity; geographical space; product space; positive sorting; product niches